Reconstructing the plant mitochondrial genome for marker discovery: a case study using Pinus. (3rd February 2017) - Donnelly, Kevin; Cottrell, Joan; Ennos, Richard A.; Vendramin, Giovanni Giuseppe; A'Hara, Stuart; King, Sarah; Perry, Annika; Wachowiak, Witold; Cavers, Stephen
Abstract: Whole‐genome‐shotgun (WGS) sequencing of total genomic DNA was used to recover ~1 Mbp of novel mitochondrial (mtDNA) sequence from Pinus sylvestris (L.) and three members of the closely related Pinus mugo species complex. DNA was extracted from megagametophyte tissue from six mother trees from locations across Europe, and 100‐bp paired‐end sequencing was performed on the Illumina HiSeq platform. Candidate mtDNA sequences were identified by their size and coverage characteristics, and by comparison with published plant mitochondrial genomes. Novel variants were identified, and primers targeting these loci were trialled on a set of 28 individuals from across Europe. In total, 31 SNP loci were successfully resequenced, characterizing 15 unique haplotypes. This approach offers a cost‐effective means of developing marker resources for mitochondrial genomes in other plant species where reference sequences are unavailable.